The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1007/bf00054936
|View full text |Cite
|
Sign up to set email alerts
|

The p185 erbB2 protein is localized on cell organelles involved in cell motility

Abstract: In a previous paper, we have shown that the c-erbB-2-encoded protein p185erbB2 is localized on the brush border of the proximal tubule kidney cells. In invasive duct cell carcinomas, the labeling was most obvious on the villous plasma membrane protrusions. From these observations the hypothesis was raised that p185erbB2 could play a role in motility. To test this hypothesis, we quantified its distribution on the microvilli and plasma membrane protrusions and on the straight parts of the cell membrane after imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…To address this question and characterize trastuzumab and ErbB2 localization more precisely, we performed 1) quantitative immunoelectron microscopy using antibodies to detect either trastuzumab or the cytoplasmic tail of ErbB2 or to improve sensitivity in single labeling experiments, and 2) silver enhancement of 1 nm NG-trastuzumab. Surface-bound trastuzumab, like ErbB2 (see below) and in line with previous observations (De Potter and Quatacker, 1993;Hommelgaard et al, 2004), was enriched on microvillus-like protrusions, was found occasionally within clathrin-coated pits, and was absent from noncoated plasma membrane invaginations (Figure 8, A Figure 5B). Internalized trastuzumab was found mainly on small (Յ60 nm) tubules and vesicles adjacent to endosomal vacuoles and dispersed in the cytoplasm (Figure 8, C-E, and Table 1).…”
Section: Electron Microscopy Reveals Trastuzumab and Erbb2 In The Recsupporting
confidence: 90%
“…To address this question and characterize trastuzumab and ErbB2 localization more precisely, we performed 1) quantitative immunoelectron microscopy using antibodies to detect either trastuzumab or the cytoplasmic tail of ErbB2 or to improve sensitivity in single labeling experiments, and 2) silver enhancement of 1 nm NG-trastuzumab. Surface-bound trastuzumab, like ErbB2 (see below) and in line with previous observations (De Potter and Quatacker, 1993;Hommelgaard et al, 2004), was enriched on microvillus-like protrusions, was found occasionally within clathrin-coated pits, and was absent from noncoated plasma membrane invaginations (Figure 8, A Figure 5B). Internalized trastuzumab was found mainly on small (Յ60 nm) tubules and vesicles adjacent to endosomal vacuoles and dispersed in the cytoplasm (Figure 8, C-E, and Table 1).…”
Section: Electron Microscopy Reveals Trastuzumab and Erbb2 In The Recsupporting
confidence: 90%
“…neu /ErbB2, which has been implicated in tumor cell metastasis, is proposed to play a role in the regulation of cell structure and motility (6). The receptor is concentrated on microvilli in SK-BR-3 breast cancer cells.…”
mentioning
confidence: 99%
“…The receptor is concentrated on microvilli in SK-BR-3 breast cancer cells. Activation of its phosphorylation leads to cell spreading, enlargement of microvilli, formation of pseudopodia, and aggregation of the p185 at the plasma membrane protrusions and pseudopodia (6). A specific role for p185 neu /ErbB2 in these microfilament-dependent processes known to enhance metastatic capability of tumor cells was shown in p185 neuoverexpressing transfectants of NCI-H460 lung carcinoma cells (7).…”
mentioning
confidence: 99%
“…The association between the erbB2 receptor and motility in the SKBR-3 cell line has also been demonstrated in previous studies. A 50 kd protein isolated from COLO-16 cells, which has not been characterized but has been suggested to be a member of the heregulin family, stimulated motility of SKBR-3 cells (57) and aggregation of phosphorylated erbB2 receptor in pseudopodia and membrane ruffles (58). EGF has also been shown to induce formation of lamellopodia and act as a chemotactic agent for a metastatic mammary adenocarcinoma cell line derived from the rat (59).…”
Section: Discussionmentioning
confidence: 99%